Mapping the US Census Data Using the TIGER/Line Shapefiles: AE557/AE557, 05/2021 - Her, Young Gu; Yu, Ziwen (EDIS, 2021)
This publication introduces the TIGER/Line Shapefile datasets and demonstrates how we can extract and map spatial information from the US Census data using the shapefiles. Written by Young Gu Her and Ziwen Yu, and published by the UF/IFAS Department of Agricultural and Biological Engineering, May 2021.